POLITENESS IN THE SPEECH OF CHARACTER IN "KEY EYE by HELLA S. HAASSE" NOVEL (Content Analysis Methods) - Irfan Firnanda (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2018)
AbstractThe purpose of this research is to comprehend the language comprehensively in the novel "Key Eyeâ€ by HELLA S. HAASSE. This research uses qualitative research with content analysis method. Data were collected through speeches of characters in novels, observations, and recordings. Analysis and interpretation of data shows that politeness in the speech of the character in the novel â€œKey eye by HELLA S. HAASSE" divided into positive politeness and negative politeness, as well as the maxim according to Geoffrey Leech. These findings can be a recommendation for students to understand the comprehensive politeness by reading the novel "The Key Eye by HELLA S. HAASSEâ€ as an alternative source of learning on politeness. This research is also recommended to the next researcher to use this research as a reference in his research.Key words: Politeness, Maxim, Novel, Content analysis.